Multimedia learning: A courseware development project for a De La Salle Philippines institution - Ulit, Estefanie D. (Animo Repository, 2010)
The Instructional Systems Technology (IST) specialization in De La Salle University in Manila aims to train students in using information and communication technologies and applying learning principles and theories to bridge gaps and support emerging trends in education. Students, who are taking up this specialization under the Bachelor of Science degree in Computer, go through a class in courseware development. It is an integration course where previous knowledge and skills learned in IST and Education courses will be applied to the development of a self-teaching/self-assessing instructional tool. Those enrolled in the class learn how to apply instructional design principles and use different multimedia tools in order to develop various forms of instructional materials for a selected topic or subject area. The final project entails the students to design and develop a courseware-a multimedia application that serves as an instructional tool for self-paced learning. This requirement allows the students to exhibit their creative skills in digital art as well as their capabilities in designing effective multimedia materials for instruction and learner assessment.A number of factors have to be considered in coming up with an effective instructional material, which makes use of the right media blend, while still considering both learning and learner requirements. This requires the students to go through an organized media design and development process involving the accomplishment of a series of interrelated milestones, which have been based on past instructional development methodologies and techniques. The resulting methodology consists of the following phases: topic selection, identifying learning objectives/outcomes, creating storyboards and screen designs, scriptwriting, developing and integrating the media, prototype presentation, user acceptance testing, and final project evaluation.All student groups will submit the final coursewares at the end of the trimester. A project rubric will be used to evaluate the student outputs according to certain criteria. There are six (6) criteria to be considered in the courseware evaluation: content, media, instructional design, interactivity, technical functionality, and project presentation.The courseware development project is a joint effort between the students of the IST specialization and De La Salle University's Social Action Committee of the College of Computer Studies. The students will specifically create coursewares based on the Grade 5 Elementary Science curriculum of Jaime Hilario Integrated School-La Salle (JHIS-LS). JHIS-LS, a member of De La Salle Philippines, is an institution in primary and secondary education located in Bagac, Bataan. It was opened by the De La Salle Brothers in 2006 to cater to the less-fortunate community in that area of Central Luzon. The school's curriculum generally aims to instill concern and awareness for their community and the environment.